Salivary osmolality measured by MX3 hydration testing system demonstrates high reliability but limited validity in elite athlete hydration assessment - Stefan Pettersson; Lykke Tamm; Stig Mattsson; Anton Kalén (PLoS ONE, 2026)
Accurate assessment of hydration is essential for both athletic performance and health, yet remains challenging outside controlled settings. This study evaluated the validity and reliability of salivary osmolality (SOSM), measured using a handheld osmometer (MX3 Hydration Testing System), as a marker of morning hydration status in elite athletes. A total of 230 paired fasted-morning saliva and urine sample sets from 118 Olympic-level athletes (57% female; age 27 ± 5 years; BMI 24 ± 2) were included in the analyses. Urine specific gravity (USG) served as the reference. Validity was examined using ICC(3,1), ROC analysis, and Cohen’s κ, and test–retest reliability was assessed from three repeated SOSM readings from the same saliva sample. SOSM showed no meaningful correspondence with USG (ICC = 0.00; 95% CI [−0.13, 0.13]) and no meaningful classification agreement (κ = −0.02; 95% CI [−0.15, 0.10]). Diagnostic accuracy was poor across all examined threshold comparisons, with AUCs of 0.40–0.49, indicating chance-level to worse-than-chance discrimination, sensitivity 40–69%, and specificity 23–65%. By contrast, within-sample repeated SOSM measurements were highly consistent (ICC = 0.93; 95% CI [0.91, 0.94]), with a standard error of measurement of 7.9 mOsm and a minimal detectable change (MDC 90 ) of 18.4 mOsm. These findings indicate that the MX3 device is repeatable when reading the same saliva sample, but SOSM lacks validity as a stand-alone marker of first-morning hydration status in elite athletes under free-living conditions.